Secondary battery negative electrode, preparation method thereof, secondary battery, battery module, battery pack and power-using device

By combining the polymer melt with silicon nanoparticles, and forming porous silicon negative electrode sheets through tensile pore formation and high-temperature carbonization, the mechanical stress problem of silicon-based materials due to volume changes in lithium-ion batteries is solved, and high-quality The performance and low-cost secondary battery negative electrode simplifies the production process.

CN115832228BActive Publication Date: 2025-02-21CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202210055371.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-01-18
Publication Date
2025-02-21
Estimated Expiration
2042-01-18

AI Technical Summary

Technical Problem

现有技术中,硅基材料在锂离子电池的充放电循环中因体积变化导致机械应力大,导致材料粉化坍塌,影响电子传输和锂电池容量,且制备方法复杂,难以大规模连续量产 .

Method used

By directly combining the polymer melt (such as PP or PE) with silicon nanoparticles, a matrix covering silicon nanometers is formed, and a porous silicon negative electrode sheet is formed through steps such as stretching and high-temperature carbonization. The negative electrode sheet has no rebound Problem: It comes with a support structure to adapt to the expansion of the extreme sheet during aging and simplify the production process.

Benefits of technology

The high performance of the negative electrode of the secondary battery is achieved, the DC resistance is reduced, the battery power is improved, the formation of solid electrolyte interface film on the silicon surface is avoided, the circulation performance of the battery is extended, and the manufacturing cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115832228B_ABST
    Figure CN115832228B_ABST
Patent Text Reader

Abstract

The present application relates to a method for preparing a negative electrode of a secondary battery, comprising: (1) dispersing silicon nanoparticles into a carbonizable polymer melt to form a mixture containing silicon nanoparticles and a carbonizable polymer melt; (2) casting the mixture to form a carbonizable polymer film containing silicon nanoparticles; (3) stretching the carbonizable polymer film to form a carbonizable polymer film with a mesh structure containing voids inside; and (4) carbonizing the carbonizable polymer film formed in step (3) to obtain the negative electrode of the secondary battery. In the present application, the method can continuously produce a self-supporting carbon-coated silicon secondary battery negative electrode, which has no rebound problem and has its own supporting structure, providing space for the expansion of the pole piece during the later aging process, thereby solving the problem of cracks that may occur in the pole piece.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of manufacturing lithium-ion battery silicon negative electrodes, and specifically relates to a secondary battery negative electrode, a preparation method thereof, a secondary battery, a battery module, a battery pack, and an electrical device. Background Art

[0002] Secondary batteries (e.g., lithium-ion batteries) have the advantages of high energy density, low self-discharge, no memory effect, wide operating voltage range, long service life, and no environmental pollution. They are currently the main power source for new energy vehicles. The key electrode materials of lithium-ion batteries are the ultimate determining factor in battery performance, among which the negative electrode materials play a vital role in improving the performance of lithium-ion batteries. However, the specific capacity of traditional graphite negative electrodes is close to the theoretical value of 372mAh / g, and there is little room for improvement, so the development of high-performance new electrode materials has become a research hotspot. Silicon has an ultra-high theoretical specific capacity (4200mAh / g) and a low lithium desorption potential (<0.5V), and the voltage platform of silicon is slightly higher than that of graphite. It is difficult to cause surface lithium precipitation during charging, and has better safety performance. However, the volume change of silicon during charging and discharging is as high as 300%, which makes it bear a large mechanical force during the charge and discharge cycle and gradually pulverize and collapse, affecting the connection between the active material and the current collector, which is not conducive to electron transmission; on the other hand, it makes the solid electrolyte interface film formed between the silicon-based material and the electrolyte gradually thicken, which is not conducive to improving the capacity of the lithium battery, causing the cycle performance of the lithium battery to drop sharply. The existing technology has the problem of complex process and difficulty in large-scale continuous mass production. Therefore, improving the preparation method of the negative electrode of the carbon-coated silicon secondary battery is still a problem to be solved. Summary of the invention

[0003] In order to solve the problems existing in the prior art, the present application subverts the traditional process and concept of traditional secondary battery (for example, lithium-ion battery) production. It directly compounds a polymer melt (for example, PP or PE) with silicon nanoparticles to form a matrix that wraps silicon nanoparticles, and then forms a porous silicon negative electrode sheet through steps such as stretching and pore formation and high-temperature carbonization. The negative electrode sheet has no rebound problem, excellent conductivity, and a self-supporting structure, which is conducive to later expansion. The production structure is greatly simplified, which not only solves the problem of ultra-thick expansion of traditional battery cells, but also proposes a new production process, greatly reduces manufacturing costs, and revolutionizes the traditional concept of secondary battery production technology.

[0004] According to a first aspect of the present application, a method for preparing a negative electrode of a secondary battery is provided, comprising:

[0005] (1) dispersing silicon nanoparticles into a carbonizable polymer melt to form a mixture comprising silicon nanoparticles and a carbonizable polymer melt;

[0006] (2) casting the mixture to form a carbonizable polymer film containing silicon nanoparticles;

[0007] (3) stretching the carbonizable polymer film to form a carbonizable polymer film having a network structure and containing voids therein;

[0008] (4) Carbonizing the carbonizable polymer film formed in (3) to obtain the secondary battery negative electrode.

[0009] In the present application, the method directly compounds a polymer melt (for example, PP or PE) with silicon nanoparticles, and then forms a porous silicon negative electrode plate through steps such as stretching and pore formation and high-temperature carbonization. The negative electrode plate has no rebound problem and has its own supporting structure, which provides space for the expansion of the plate during the later aging process, thereby solving the problem of cracks that may occur in the plate.

[0010] In an embodiment of the present application, the weight average particle size of the silicon nanoparticles ranges from 5 nanometers to 200 nanometers; and the average pore size of the voids ranges from 15 nanometers to 2000 nanometers. By controlling the weight average particle size of the silicon nanoparticles and the average pore size of the voids formed after stretching, the method described in the present application ensures that a sufficient self-supporting network structure is provided, so that the secondary battery system has good conductivity, reduces the direct current resistance (DCR) of the secondary battery, and improves the battery power.

[0011] In the embodiment of the present application, the carbonization temperature range is between 800°C and 1400°C, and the carbonization time is between 20 minutes and 2 hours. In the present application, the carbonization temperature range and carbonization time can ensure that the polymer melt is carbonized as completely as possible, so that the secondary battery system has good conductivity; at the same time, it avoids the reduction of the diameter of the carbon fiber and the reduction of the strength, which affects the quality of the negative electrode and the battery performance in the subsequent cycle charge and discharge process.

[0012] In an embodiment of the present application, the carbonization temperature is first increased gradually during the entire carbonization time to a temperature of 800°C-1400°C, and then decreased gradually. In an embodiment of the present application, the carbonization temperature is increased by a gradient of 5°C / min-50°C / min. By this method of increasing the temperature gradient and then decreasing the temperature gradient, it is possible to ensure that the polymer melt is carbonized as completely as possible and maintain sufficient strength of the self-supporting structure.

[0013] In an embodiment of the present application, the carbonizable polymer includes polyolefins, polyesters, polyimides, polyamides and various cellulose materials. In an embodiment of the present application, the polyolefins include polyethylene (PE), polypropylene (PP) or a combination thereof.

[0014] According to the second aspect of the present application, a secondary battery negative electrode is provided, which is prepared by the method described in the present application. In the present application, the method is to directly compound a polymer melt (for example, PP or PE) with silicon nanoparticles, and then form a porous silicon negative electrode pole piece through steps such as stretching and pore formation, high-temperature carbonization, etc. The negative electrode pole piece has no rebound problem and has its own supporting structure, which provides space for the pole piece to expand during the later aging process, and solves the problem of cracks that may occur in the pole piece. Moreover, by controlling the weight-average particle size of the silicon nanoparticles and the average pore size of the voids formed after stretching, the method described in the present application ensures that a sufficient self-supporting mesh structure is provided, which can make the secondary battery system have better conductivity, reduce the DC resistance (DCR) of the secondary battery, and improve the battery power.

[0015] According to a third aspect of the present application, a secondary battery is provided, characterized in that the secondary battery includes a secondary battery negative electrode, especially a carbon-coated silicon secondary battery negative electrode.

[0016] According to a fourth aspect of the present application, a battery module is provided, comprising the secondary battery described in the present application.

[0017] According to a fifth aspect of the present application, a battery pack is provided, comprising the secondary battery or battery module described in the present application.

[0018] According to the sixth aspect of the present application, an electrical device is provided, which includes the secondary battery, battery module or battery pack described in the present application, and the secondary battery or the battery module or the battery pack is used as a power source for the electrical device or an energy storage unit for the electrical device.

[0019] Compared with the prior art, the method described in the present application does not require the use of carboxymethyl cellulose (CMC), simplifies the traditional production formula, saves manufacturing costs, and can continuously produce a self-supporting carbon-coated silicon secondary battery negative electrode. The negative electrode pole piece has no rebound problem and has its own supporting structure, which provides space for the pole piece to expand during the later aging process and solves the problem of cracks that may occur in the pole piece. Moreover, by controlling the weight-average particle size of the silicon nanoparticles and the average pore size of the voids formed after stretching, the method described in the present application ensures that a sufficient self-supporting mesh structure is provided, which can make the secondary battery system have better conductivity, reduce the direct current resistance (DCR) of the secondary battery, and improve the battery power. At the same time, the carbon-coated silicon secondary battery negative electrode can avoid the formation of a solid electrolyte interface (SEI) film on the silicon surface.

[0020] These and other features and advantages will become apparent by reading the following detailed description and by reference to the associated drawings.It is to be understood that the foregoing general description and the following detailed description are illustrative only and are not restrictive of the aspects of what is claimed. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 It is a flow chart of preparing a carbon-coated silicon secondary battery negative electrode in a specific embodiment of the present application.

[0022] Figure 2 This is a comparison chart of the cycle capacity attenuation of different silicon negative electrodes in the test examples of this application.

[0023] Figure 3 It is a schematic diagram of one embodiment of the secondary battery of the present application.

[0024] Figure 4 yes Figure 3 An exploded view of a secondary battery is shown.

[0025] Figure 5 It is a schematic diagram of an embodiment of a battery module of the present application.

[0026] Figure 6 It is a schematic diagram of an embodiment of the battery pack of the present application.

[0027] Figure 7 yes Figure 6 Exploded view of the battery pack shown.

[0028] Figure 8 This is a schematic diagram of one embodiment of a device using the secondary battery of the present application as a power source.

[0029] Description of reference numerals:

[0030] 1. Battery Pack

[0031] 2. Upper box

[0032] 3. Lower box

[0033] 4. Battery module

[0034] 5. Secondary battery

[0035] 51. Shell

[0036] 52. Electrode assembly

[0037] 53. Cover DETAILED DESCRIPTION

[0038] The present application is described in detail below in conjunction with the accompanying drawings, and the features of the present application will be further revealed in the following specific description.

[0039] "Scope" disclosed herein is defined in the form of lower limit and upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a particular range. The scope defined in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a particular parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0040] In this application, if there is no special description, all embodiments and preferred embodiments mentioned herein can be combined with each other to form a new technical solution. In this application, if there is no special description, all technical features and preferred features mentioned herein can be combined with each other to form a new technical solution.

[0041] In this application, unless otherwise specified, the terms "include" and "comprising" mentioned herein may be open-ended or closed-ended. For example, the terms "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0042] In the description herein, unless otherwise specified, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0043] In the prior art, the preparation method of hollow-structured silicon-carbon negative electrode materials has the problem of being unable to be continuously mass-produced. This is because nano-silicon needs to undergo two steps of low-residual carbon source coating and organic cracking carbon source coating, which is relatively cumbersome; moreover, the coating thickness of the low-residual carbon source and the coating thickness of the organic cracking carbon source are difficult to accurately control, the product specification repeatability is low, and the quality is difficult to guarantee. Another prior art includes grafting an initiator on the surface of a silicon sphere, grafting a completely thermally decomposable polymer as a medium layer through active free radical polymerization, forming a space after thermal decomposition, and then polymerizing the outside of the medium layer to form a carbon layer precursor, and the carbon layer precursor is pyrolyzed and carbonized to obtain a shell carbon. However, in this method, the medium layer polymer is grafted to the surface of the silicon sphere through active free radical polymerization, which is difficult to process; and the medium layer and the coating carbon layer are both temporarily polymerized, which has a high process risk. Therefore, this technology also has the problem of being unable to be continuously mass-produced.

[0044] However, in the present application, the method for preparing the negative electrode of the carbon-coated silicon secondary battery is to directly compound the polymer melt (for example, PP or PE) with silicon nanoparticles, and then form a porous silicon negative electrode plate by stretching pores, high-temperature carbonization and other steps. The negative electrode plate has no rebound problem and has its own support structure, which provides space for the expansion of the plate during the later aging process, and solves the problem of cracks that may occur in the plate. By using the above-mentioned negative electrode plate, the present application can provide a higher energy density battery design, and there is no rebound or only low rebound in the production process of the plate and the charging and discharging process of the secondary battery; and there is no over-thickness problem caused by improper production control in the production process of the secondary battery, the production process is simplified (the traditional method includes premixing-stirring-coating-cold pressing-die cutting, etc., and the new technology includes melting-casting stretching-high-temperature carbonization), the production equipment and manufacturing costs are reduced, the carbon base has excellent conductivity, the DCR is reduced, the power performance is improved, and the expansion force is improved, the cycle performance of the secondary battery cell is improved, and the first effect of the secondary battery cell is improved.

[0045] In the present application, silicon nanoparticles are dispersed in a polymer melt to form a mixture containing silicon nanoparticles and a polymer melt. The silicon nanoparticles can be purchased in bulk, and the weight-average particle size of the silicon nanoparticles can be from a few nanometers to several hundred nanometers. In a specific embodiment of the present invention, the weight-average particle size of the silicon nanoparticles can be within a numerical range consisting of any two of the following values ​​as end values: 5 nanometers, 10 nanometers, 20 nanometers, 50 nanometers, 80 nanometers, 100 nanometers, 150 nanometers, 200 nanometers, 250 nanometers, 300 nanometers, 350 nanometers, 400 nanometers, 450 nanometers, 500 nanometers. It should be particularly emphasized that although the above values ​​are listed in parallel, it does not mean that the numerical range consisting of any two of the above values ​​as end points can obtain equivalent or similar performance. This also applies to the numerical range mentioned below. Regarding the preferred embodiment of the present application, selection is made based only on the specific discussion below and specific experimental data. In an optional embodiment of the present application, the weight-average particle size of the silicon nanoparticles ranges from 5 nanometers to 200 nanometers.

[0046] In the present application, the polymer melt may be a hydrocarbon polymer commonly used in secondary battery separators. In one embodiment of the present application, the polymer melt material may include polyolefins, polyesters, polyimides, polyamides and various cellulose materials. In a preferred embodiment, the polymer melt material may include polyethylene (PE), polypropylene (PP) or a combination thereof. In the present application, the melting of the polymer and the stretching and pore-forming process of the polymer membrane may use mature processes or technologies in the art, which are convenient for regulating the ratio of silicon nanoparticles to polymers and the size of the voids (holes) encapsulating the silicon nanoparticles.

[0047] In the present application, the mixture is cast to form a polymer film. The casting process and equipment can be the same as the casting process and equipment used in the manufacturing process of the secondary battery separator. However, slightly different from the manufacturing process of the secondary battery separator is that the film formed by casting the polymer melt and silicon nanoparticles is the precursor of the negative electrode of the secondary battery, and its thickness is usually larger than the separator precursor. Considering the thickness reduction in the subsequent stretching process and the thickness reduction in the subsequent carbonization process, the film thickness formed by casting the mixture containing silicon nanoparticles and polymer melt can be 100-300 microns. In a specific embodiment of the present invention, the thickness of the film formed by casting can be within the numerical range formed by any two of the following values ​​as end values: 100 microns, 150 microns, 200 microns, 250 microns, 300 microns. In an optional embodiment of the present application, the thickness of the film formed by casting can be 200 microns. In an embodiment of the present invention, the width of the film formed by casting can be determined according to the width of the mold equipment, and can be subsequently cut into negative electrode sheets of ideal width.

[0048] In the present application, the polymer membrane is stretched to form a mesh structure containing voids inside the polymer membrane. The stretching process and equipment can be the same as the stretching process and equipment used in the manufacturing process of the secondary battery separator. The degree of stretching is mainly determined by two aspects: (1) the particle size of the selected silicon nanoparticles. The size of the voids (holes) formed after stretching must be several times larger than the volume of the silicon nanoparticles; (2) the thickness of the fiber after stretching. Unlike the degree of stretching of the separator, the polymer framework fiber formed by this stretching must have a certain strength. On the one hand, it is prepared for the subsequent manufacture of a negative electrode with a certain strength. On the other hand, it can resist the volume expansion effect of the silicon nanoparticles in the subsequent cycle process. In order to meet the above strength requirements, in a specific embodiment of the present invention, the multiple relationship between the average pore size of the voids and the weight-average particle size of the silicon nanoparticles can be within the numerical range formed by any two of the following values ​​as end values: 2 times, 3 times, 5 times, 8 times, 10 times, 13 times, 15 times, 18 times, 20 times, 25 times, 30 times. In an optional embodiment of the present application, the average pore size of the voids is 3-10 times the weight average particle size of the silicon nanoparticles.

[0049] In a specific embodiment of the present invention, the average pore size of the voids can be within a numerical range formed by any two of the following numerical values ​​as end values: 15 nanometers, 20 nanometers, 25 nanometers, 50 nanometers, 100 nanometers, 300 nanometers, 500 nanometers, 700 nanometers, 900 nanometers, 1000 nanometers, 1200 nanometers, 1400 nanometers, 1500 nanometers, 1800 nanometers, 2000 nanometers.

[0050] In the present application, a polymer film containing a mesh structure is carbonized to provide a carbon-coated silicon secondary battery negative electrode. In the present application, the equipment for the carbonization process can refer to the process equipment for the baking process after the coating of the secondary battery anode electrode. In a specific embodiment, a series of ovens are set, and the oven temperature can be gradually increased and then gradually decreased, and the stretched polymer film is slowly transported through this series of ovens. The temperature of the oven is usually set to above 800°C. In the present application, if the oven temperature is set too low, the polymer carbonization is incomplete, affecting the conductivity; if the oven temperature is set too high, the polymer carbonization time is too long, the diameter of the carbon fiber is reduced, and the strength is reduced, affecting the quality of the secondary battery negative electrode and the battery performance during subsequent cyclic charge and discharge.

[0051] In a specific embodiment of the present invention, the carbonization temperature may be within a numerical range consisting of any two of the following values ​​as end values: 800°C, 850°C, 900°C, 950°C, 1000°C, 1100°C, 1200°C, 1300°C, 1400°C, 1500°C. In an optional embodiment of the present application, the carbonization temperature range is between 800-1400°C. In a specific embodiment of the present invention, the carbonization time may be within a numerical range consisting of any two of the following values ​​as end values: 20 minutes, 30 minutes, 40 minutes, 50 minutes, 60 minutes, 70 minutes, 80 minutes, 90 minutes, 100 minutes, 110 minutes, 120 minutes, 3 hours, 4 hours, 5 hours. In an optional embodiment of the present application, the carbonization time is between 20 minutes and 2 hours.

[0052] In a specific embodiment, the temperature of the carbonization is first increased gradually during the entire carbonization time to a temperature of 800-1400°C, and then decreased gradually. In a specific embodiment of the present invention, the temperature increase gradient of the carbonization can be within a numerical range consisting of any two of the following values ​​as end values: 5°C / minute, 15°C / minute, 25°C / minute, 35°C / minute, 45°C / minute, 50°C / minute, 70°C / minute, 100°C / minute. In an optional embodiment of the present application, the temperature of the carbonization is increased with a gradient of 5°C / minute-50°C / minute.

[0053] In the following, the performance improvement brought about by the method for preparing a carbon-coated silicon secondary battery negative electrode of the present application is characterized mainly based on secondary batteries, especially lithium-ion secondary batteries. However, it should be emphasized here that the method for preparing a carbon-coated silicon secondary battery negative electrode of the present application can be used for any electrical device including a carbon-based electrode, and the electrical device can benefit therefrom.

[0054] exist Figure 1 In the figure, a process flow chart of preparing a negative electrode of a carbon-coated silicon secondary battery of the present application is shown. Figure 1 As shown, the process includes the following four steps:

[0055] Step 1, hot melt (see Figure 1 Middle A)

[0056] The silicon nanoparticles (Si) and the polymer solid particles (PP / PE) are melted together so that the silicon nanoparticles are evenly dispersed in the polymer hot melt liquid;

[0057] Step 2, casting (see Figure 1 Middle B)

[0058] Similar to the casting process in the process of manufacturing the separator in the secondary battery in the art, the polymer mixture (solid solution) containing silicon nanoparticles is cast into a film to facilitate subsequent processing. The setting of the process parameters in this step determines the length, width and thickness of the subsequent finished film.

[0059] Step 3: Stretch (see Figure 1 Middle C)

[0060] The film formed after casting still maintains a dense internal structure, and there is no space around the nanoparticles. After stretching the film, a network structure with many gaps will be formed inside the polymer, and space will also be formed around the silicon nanoparticles due to stretching deformation. These gaps and spaces are the reserved gaps for the subsequent carbon-coated silicon nanoparticles. The reserved space inside the polymer is more conducive to the transmission of electrolyte and lithium ions, and the space around the silicon nanoparticles can be used as a reserved space for volume expansion in the subsequent cycle process.

[0061] Step 4: High temperature carbonization (see Figure 1 Middle D)

[0062] The polymer-coated silicon structure obtained from step 1 to step 3 still has poor conductivity, so the polymer needs to be carbonized to become a carbon-coated silicon structure. This high-temperature carbonization process of the polymer needs to be carried out under the protection of an argon atmosphere. The specific carbonization temperature and carbonization time need to be carefully adjusted. Too low a carbonization temperature will result in poor conductivity, and excessive carbonization will result in a high degree of carbon crystallization, resulting in the disappearance of voids.

[0063] Secondary battery

[0064] In one embodiment of the present application, a secondary battery is provided, which can be a lithium ion secondary battery, a potassium ion secondary battery, a sodium ion secondary battery, a lithium sulfur battery, etc., and is particularly preferably a lithium ion secondary battery. The secondary battery of the present application includes a positive electrode (pole sheet), a negative electrode (pole sheet), a separator, an electrolyte / liquid, etc. During the battery charge and discharge process, active ions are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet.

[0065] [Positive electrode]

[0066] In the secondary battery of the present application, the positive electrode plate includes a positive electrode current collector and a positive electrode film layer (or positive electrode active material layer) disposed on at least one surface of the positive electrode current collector and including a positive electrode active material. For example, the positive electrode current collector has two surfaces opposite to each other in the thickness direction of itself, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector. In the secondary battery of the present application, the positive electrode current collector may be a metal foil or a composite current collector, for example, the metal foil may be an aluminum foil, and the composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material base layer. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene PP, polyethylene terephthalate PET, polybutylene terephthalate PBT, polystyrene PS, polyethylene PE and its copolymers, etc.).

[0067] In the present application, the compaction density of the positive electrode active material layer of the secondary battery is controlled to reduce the ion transmission path to improve the cycle life of the secondary battery, while at the same time, the particles of the active material will not be broken due to the high compaction density, resulting in an increase in the specific surface area (BET), leading to the side reaction of the outlet line and deteriorating the cycle life of the secondary battery to a certain extent. Usually, the compaction density of the positive electrode active material layer can be 2.0-3.6g / cm 3 In one embodiment of the present application, the compaction density of the positive electrode active material layer can be within a numerical range consisting of any two of the following values ​​as end values: 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5. In an optional embodiment of the present application, the compaction density of the positive electrode active material layer can be 2.3-3.5 g / cm 3 .

[0068] In the secondary battery of the present application, the positive electrode active material (substance) may adopt the positive electrode active material for secondary batteries known in the art. For example, the positive electrode active material may include one or more of the following: lithium-containing phosphates of olivine structure, lithium transition metal oxides and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for secondary batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O2(NCM523), LiNi 0.5 Co 0.25 Mn 0.25 O2(NCM211), LiNi 0.6 Co 0.2 Mn 0.2 O2(NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811)), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O2) and its modified compounds, etc. One or more. Examples of lithium-containing phosphates with olivine structure may include, but are not limited to, lithium iron phosphate (such as LiFePO4 (LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon. In an embodiment of the present application, the second positive electrode active material and the third positive electrode active material are the same or different, and are selected from lithium iron phosphate (LFP), lithium manganate (LMO), lithium nickel cobalt manganate (NCM), lithium cobalt oxide (LCO), lithium nickel cobalt aluminum oxide (NCA), and oxides containing active sodium ions, polyanionic materials or Prussian blue materials.

[0069] In some embodiments, the positive electrode film layer may also optionally include a binder. Non-limiting examples of binders that can be used for the positive electrode film layer may include one or more of the following: polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylate resin. In an embodiment of the present application, the first positive electrode active material layer and / or the second positive electrode active material layer each independently contain a binder selected from polyvinylidene fluoride, polyacrylic acid, polytetrafluoroethylene, polyimide and combinations thereof.

[0070] In some embodiments, the positive electrode film layer may also optionally include a conductive agent. Examples of conductive agents for the positive electrode film layer may include one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers. In an embodiment of the present application, the first positive electrode active material layer and / or the second positive electrode active material layer each independently contain a conductive agent of graphite, carbon black, acetylene black, graphene, carbon nanotubes and a combination of the above substances.

[0071] In one embodiment of the present application, the positive electrode can be prepared in the following manner: the above-mentioned components for preparing the positive electrode, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a uniform positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0072] [Negative electrode]

[0073] The secondary battery of the present application includes a carbon-coated silicon secondary battery negative electrode prepared by the method described in the present application, and the negative electrode plate includes a negative electrode collector and a negative electrode film layer (or called a negative electrode active material layer) arranged on at least one surface of the negative electrode collector.

[0074] In one embodiment of the present application, the negative electrode film layer may include a certain amount of other commonly used negative electrode active materials in addition to the negative electrode active materials described above, for example, one or more of natural graphite, other artificial graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate. The silicon-based material may be selected from one or more of elemental silicon, silicon oxide, and silicon-carbon composites. The tin-based material may be selected from one or more of elemental tin, tin oxide compounds, and tin alloys.

[0075] In the secondary battery of the present application, the negative electrode membrane comprises a negative electrode active material and an optional binder, an optional conductive agent and other optional auxiliary agents, and is usually formed by coating and drying a negative electrode slurry. The negative electrode slurry coating is usually formed by dispersing the negative electrode active material and the optional conductive agent and binder in a solvent and stirring them evenly. The solvent can be N-methylpyrrolidone (NMP) or deionized water.

[0076] As an example, the conductive agent may include one or more of superconducting carbon, carbon black (eg, acetylene black, Ketjen black), carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0077] As an example, the binder may include one or more of styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA) and carboxymethyl chitosan (CMCS). As an example, the binder may include one or more of styrene-butadiene rubber (SBR), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS). Other optional additives are, for example, thickeners (such as sodium carboxymethyl cellulose CMC-Na), PTC thermistor materials, etc.

[0078] In addition, in the secondary battery of the present application, the negative electrode plate does not exclude other additional functional layers besides the negative electrode film layer. For example, in some embodiments, the negative electrode plate of the present application may also include a conductive primer layer (e.g., composed of a conductive agent and a binder) sandwiched between the negative electrode current collector and the first negative electrode film layer and disposed on the surface of the negative electrode current collector. In some other embodiments, the negative electrode plate of the present application may also include a covering protective layer covering the surface of the second negative electrode film layer.

[0079] In the secondary battery of the present application, the negative electrode current collector may be a metal foil or a composite current collector, for example, the metal foil may be a copper foil, a silver foil, an iron foil, or a foil composed of an alloy of the above metals. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material base layer, and may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material base layer (such as a base layer made of materials such as polypropylene PP, polyethylene terephthalate PET, polybutylene terephthalate PBT, polystyrene PS, polyethylene PE and copolymers thereof).

[0080] [Electrolytes]

[0081] The electrolyte plays the role of conducting ions between the positive electrode plate and the negative electrode plate. The electrolyte can be selected from at least one of a solid electrolyte and a liquid electrolyte (i.e., an electrolyte). In some embodiments, the electrolyte uses an electrolyte. The electrolyte includes an electrolyte salt and a solvent. In some embodiments, the electrolyte salt can be selected from LiPF6 (lithium hexafluorophosphate), LiBF4 (lithium tetrafluoroborate), LiClO4 (lithium perchlorate), LiAsF6 (lithium hexafluoroarsenate), LiFSI (lithium bisfluorosulfonyl imide), LiTFSI (lithium bistrifluoromethanesulfonyl imide), LiTFS (lithium trifluoromethanesulfonate), LiDFOB (lithium difluoro oxalate borate), LiBOB (lithium dioxalate borate), LiPO2F2 (lithium difluorophosphate), LiDFOP (lithium difluoro dioxalate phosphate) and LiTFOP (lithium tetrafluoro oxalate phosphate) One or more. In one embodiment of the present application, the solvent may be selected from one or more of the following: ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE). In one embodiment of the present application, based on the total weight of the electrolyte, the content of the solvent is 60-99% by weight, such as 65-95% by weight, or 70-90% by weight, or 75-89% by weight, or 80-85% by weight. In one embodiment of the present application, based on the total weight of the electrolyte, the content of the electrolyte is 1-40% by weight, such as 5-35% by weight, or 10-30% by weight, or 11-25% by weight, or 15-20% by weight.

[0082] In one embodiment of the present application, the electrolyte may optionally contain additives. For example, the additives may include one or more of the following: negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high temperature performance, additives that improve battery low temperature performance, etc.

[0083] [Isolation film]

[0084] In one embodiment of the present application, the secondary battery further comprises a separator, which separates the anode side of the secondary battery from the cathode side, and provides selective permeation or blocking for substances of different types, sizes and charges in the system. For example, the separator can insulate electrons, physically isolate the positive and negative active substances of the secondary battery, prevent internal short circuits and form an electric field in a certain direction, and allow the ions in the battery to pass through the separator and move between the positive and negative electrodes. In one embodiment of the present application, the material used to prepare the separator may include one or more of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The separator may be a single-layer film or a multi-layer composite film. When the separator is a multi-layer composite film, the materials of each layer may be the same or different. In an embodiment of the present application, the separator is selected from polyolefin separators, polyester separators, polyimide separators, polyamide separators and cellulose separators.

[0085] In one embodiment of the present application, the positive electrode sheet, the negative electrode sheet and the separator can be made into an electrode assembly / bare cell by a winding process or a lamination process.

[0086] In one embodiment of the present application, the secondary battery may include an outer package, which can be used to encapsulate the above-mentioned electrode assembly and electrolyte. In some embodiments, the outer package of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. In other embodiments, the outer package of the secondary battery can be a soft package, such as a bag-type soft package. The material of the soft package can be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT), polybutylene succinate (PBS), etc.

[0087] The shape of the secondary battery of the present application can be cylindrical, square or any other shape. Figure 3 The secondary battery 5 is a square structure as an example. Figure 4 Shows Figure 3 The exploded view of the secondary battery 5 is shown in FIG. 5 . The outer package may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate. The bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity. The cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation film can be formed into an electrode assembly 52 through a winding process or a lamination process. The electrode assembly is encapsulated in the receiving cavity, and the electrolyte is infiltrated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more.

[0088] In one embodiment of the present application, a plurality of secondary batteries may be assembled together to form a battery module, wherein the battery module includes two or more secondary batteries, and the specific number depends on the application of the battery module and the parameters of a single battery module.

[0089] Figure 5 4 is an example of a battery module. Figure 5 In the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.

[0090] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.

[0091] In one embodiment of the present application, two or more of the above-mentioned battery modules can be assembled into a battery pack, and the number of battery modules contained in the battery pack depends on the application of the battery pack and the parameters of the individual battery modules. The battery pack may include a battery box and a plurality of battery modules disposed in the battery box, and the battery box includes an upper box body and a lower box body, and the upper box body can cover the lower box body and match well with it to form a closed space for accommodating the battery modules. Two or more battery modules can be arranged in the battery box in a desired manner.

[0092] Figure 6 and Figure 7 1 is a battery pack 1 as an example. Figure 6 and Figure 7 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3, wherein the upper box body 2 is used to cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 may be arranged in the battery box in any manner.

[0093] Electrical devices

[0094] In one embodiment of the present application, the electric device of the present application includes at least one of the secondary battery, battery module, or battery pack of the present application, and the secondary battery, battery module, or battery pack can be used as a power source of the electric device, and can also be used as an energy storage unit of the electric device. The electric device includes but is not limited to mobile digital devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.

[0095] Figure 8 The device is used as an example. The device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the device's requirements for high power and high energy density, a battery pack or a battery module can be used.

[0096] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a secondary battery may be used as a power source.

[0097] In the following, the influence of the secondary battery manufactured according to the embodiment of the present application on the performance of the electrochemical device is characterized based on specific examples, but it should be pointed out that the protection scope of the present application is defined by the claims and is not limited to the above specific embodiments.

[0098] Example

[0099] Unless otherwise stated, all raw materials used in the present invention were of analytical grade.

[0100] Example 1

[0101] First, silicon nanoparticles with a weight-average particle size of about 10nm and solid polyethylene (PE) are placed in a hot melt furnace, heated and continuously stirred until PE is completely melted, forming a suspended melt of silicon nanoparticles and polymer melt. Then, the temperature of the hot melt furnace is maintained, and the switch at the bottom of the hot melt furnace is turned on to allow the suspended melt to flow into a cast flat mold with a fixed width of 1m and a height of 5cm. The hot melt is allowed to cool naturally to form a film with a width of 1m and a thickness of 5cm. The film formed after casting is transferred to a stretching device, and the film is stretched longitudinally so that the thickness of the film is stretched from 5cm to 5mm. At this time, a mesh structure is formed inside the polymer film, and the silicon nanoparticles are wrapped inside the mesh structure, and there are a large number of gaps around the silicon nanoparticles. The stretched mesh structure is transferred to a carbonization pipeline. The pipeline is set to program heating, with a maximum temperature of 800℃ and a carbonization time of about 30 minutes. At this time, the thickness of the film is reduced to 0.3mm. At this point, the self-supporting carbon-coated nano-silicon negative electrode plate is completed, cut into 500mm width, and assembled with the cathode plate into a secondary battery.

[0102] Comparative Example 1

[0103] According to the method described in CN108258230B, a beaker containing anhydrous ethanol is first placed in an ultrasonic instrument with an ultrasonic frequency of 20000 Hz, and then silicon powder with a median particle size of 30 nm is slowly added for 1 hour to obtain a nano-silicon slurry with no sedimentation and uniform dispersion; then another beaker containing glycerol is placed on a high-temperature heating plate, the temperature is increased and heated, and after the solution boils, glucose is slowly added, the heating temperature is stabilized at 200°C, and the heating time is 1 hour, until a transparent gel is formed. After that, the cooled glucose gel was slowly added to the nano-silicon slurry. The mass ratio of glucose to nano-silicon powder was 6:1. Ultrasonic vibration was used for dispersion for 1 hour. Then, the composite slurry was added to the planetary ball mill. The ball milling beads were made of zirconium oxide, the ball milling bead diameter was 6mm, the mass ratio of ball milling beads to powder was 10:1, the ball-to-material ratio was 10:1, the ball milling speed was 800rpm, the ball milling time was 20h, and a homogeneously dispersed slurry was obtained. The dispersed slurry was then dried in a blast oven at a temperature of 80°C. Then, the dried powder was added to the fusion machine, the speed was adjusted to 1500rpm, the tool gap width was 1cm, and the fusion time was 2h to obtain the negative electrode material precursor. Finally, the negative electrode material precursor was mixed with polyethylene oxide with a particle size of 1 to 30 μm in a mixing mass ratio of 1:1, and then placed in a VC mixer, the frequency was adjusted to 1000 Hz, the mixing time was 60 min, and then placed in a high-temperature box furnace, nitrogen was introduced for protection, the temperature was raised to 700 ° C, and after keeping warm for 3 hours, it was cooled to room temperature to obtain a hollow structure silicon-carbon negative electrode material.

[0104] Comparative Example 2

[0105] According to the method described in CN106684335A, 1g of micron silicon particles is placed in a mixed solution of 100ml of concentrated sulfuric acid and hydrogen peroxide with a volume ratio of 7:3 at room temperature, stirred for 2h, and centrifuged and washed for separation 3 times to obtain micron silicon particles with hydroxyl groups on the surface after hydrophilic treatment. 1g of silicon particles obtained in step 1) is ultrasonically dispersed in a mixed solution of 7ml of 28% ammonia water and 100ml of ethanol, and a mixed solution of 1g of dodecyl triethoxysilane and 10ml of ethanol is added dropwise to the suspension of silicon balls in a 40°C water bath. After the addition is completed, the reaction is continued for 24h, and the product is centrifuged three times using ethanol to obtain silicon particles with surface grafted silane coupling agent. 1g of silicon particles obtained in step 2) is added to an acetone solution (50wt.%) of polymethyl methacrylate with a Mw of 7000-10000, the mass ratio of silicon to polymethyl methacrylate is 1:10, ball milling is performed for 10h, and the obtained suspension is spray-dried to obtain a granular product of polymer-coated silicon spheres. 1g of polymer silicon particles obtained in step 3) is mixed evenly with 1.33g of carboxymethyl cellulose in deionized water and refluxed for 4h, and then the solvent is distilled off at atmospheric pressure to obtain silicon particles with the surface coated with carboxymethyl cellulose and the inner layer coated with polyethylene oxide. The silicon particles obtained in step 4) are oxidatively cross-linked at a temperature of 150°C in air for 10h, and pyrolyzed at a temperature of 800°C in an inert gas in a tubular furnace for 10min to obtain a silicon core@void@carbon shell material with a silicon-carbon ratio of 1:1, i.e., a micron-sized silicon negative electrode for lithium-ion batteries.

[0106] Test Case

[0107] The self-supporting carbon-coated nano-silicon negative electrode sheet prepared in Example 1 (EX.1) and the nano-silicon and carbon-coated nano-silicon particle negative electrode sheets prepared in Comparative Examples 1-2 (CE1 and CE2) were assembled into secondary batteries. The discharge specific capacity and cycle performance of each secondary battery were tested as described below. The test results are shown in Figure 2 It can be seen that the self-supporting carbon-coated nano-silicon negative electrode sheet described in Example 1 solves the problem of poor silicon negative electrode cycle to a large extent, and compared with traditional nano-silicon and carbon-coated nano-silicon particles, the silicon capacity is retained to a greater extent.

[0108] Cyclic performance test

[0109] Place the prepared hard shell battery / secondary battery on the Xinwei machine. At a temperature of 25°C, charge at a constant current rate of 0.5C to the rated voltage, let it stand for 5 minutes, then discharge at a constant current rate of 0.5C to the cut-off voltage, record the discharge specific capacity, and let it stand for another 5 minutes. Repeat this cycle until the number of cycles reaches 100, and record the discharge specific capacity at this time.

[0110] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A method for preparing a negative electrode of a secondary battery, comprising: (1) dispersing silicon nanoparticles into a carbonizable polymer melt to form a mixture comprising silicon nanoparticles and a carbonizable polymer melt; (2) casting the mixture to form a carbonizable polymer film containing silicon nanoparticles; (3) stretching the carbonizable polymer film to form a carbonizable polymer film having a network structure and containing voids therein; and (4) Carbonizing the carbonizable polymer film formed in step (3) to obtain the secondary battery negative electrode.

2. The preparation method according to claim 1, characterized in that: The weight average particle size of the silicon nanoparticles ranges from 5 nanometers to 200 nanometers; and the average pore size of the voids ranges from 15 nanometers to 2000 nanometers.

3. The preparation method according to claim 1 or 2, characterized in that: The carbonization temperature ranges from 800° C. to 1400° C., and the carbonization time ranges from 20 minutes to 2 hours.

4. The preparation method according to claim 1 or 2, characterized in that: The carbonization temperature first increases gradually during the entire carbonization time to a temperature of 800° C.-1400° C., and then decreases gradually.

5. The preparation method according to claim 4, characterized in that: The carbonization temperature was increased in a gradient of 5° C. / min to 50° C. / min.

6. The preparation method according to claim 1 or 2, characterized in that: The carbonizable polymers include polyolefins, polyesters, polyimides, polyamides and various cellulosic materials.

7. The preparation method according to claim 6, characterized in that: The polyolefins include polyethylene (PE), polypropylene (PP) or a combination thereof.

8. A secondary battery negative electrode, characterized in that: Prepared by the method according to any one of claims 1 to 7.

9. A secondary battery, characterized in that: The secondary battery comprises the secondary battery negative electrode according to claim 8.

10. A battery module, characterized in that: The secondary battery according to claim 9 is included.

11. A battery pack, characterized in that: The invention comprises the secondary battery according to claim 9 or the battery module according to claim 10.

12. An electrical device, characterized in that: It comprises the secondary battery according to claim 9, the battery module according to claim 10, or the battery pack according to claim 11, wherein the secondary battery, the battery module or the battery pack is used as a power source for the electrical device or an energy storage unit for the electrical device.

Citation Information

Patent Citations

  • Preparation method of micron silicon negative electrode for lithium ion batteries

    CN106684335A

  • A hollow silicon-carbon anode material for lithium-ion batteries and its preparation method

    CN108258230B

  • Core-shell silicon carbon composite negative electrode material for high-capacity type lithium ion battery and preparation method therefor

    CN105489855A

  • Self-supporting nitrogen-doped porous carbon-coated silicon nanofiber material for negative electrode of lithium ion battery as well as preparation method and application of self-supporting nitrogen-doped porous carbon-coated silicon nanofiber material

    CN113629251A